2007
DOI: 10.1088/0957-4484/18/48/485702
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cathode structure on the field emission properties of individual multi-walled carbon nanotube emitters

Abstract: We report the effect of cathode structure on the field emission properties of individual carbon nanotubes. Experimental field emission data are obtained for two well-defined cathode structures: a multi-walled carbon nanotube (MWNT) attached to an etched Ni metal wire and a MWNT attached to a flat Ni-coated Si microstructure. We observed different macroscopic turn-on fields of 1.6 and 2.5 V µm−1, respectively, for the aforementioned experimental structures. This effect is investigated by detailed finite element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 21 publications
1
27
0
Order By: Relevance
“…Figure 3a shows the field emission I-V characteristics of a CPA with a turn-on voltage of 0.9 V/μm. This low turn-on field of CPAs is comparable to values typically reported for individual CNT emitters [7,8].…”
Section: Sponsor/monitor's Report Number(s)supporting
confidence: 82%
“…Figure 3a shows the field emission I-V characteristics of a CPA with a turn-on voltage of 0.9 V/μm. This low turn-on field of CPAs is comparable to values typically reported for individual CNT emitters [7,8].…”
Section: Sponsor/monitor's Report Number(s)supporting
confidence: 82%
“…Previous research has demonstrated that nanotube field emission electron source parameters such as the turn-on voltage, field enhancement factor, and beam profile are greatly influenced by the nanotube tip structure [10][11][12]. Our group and others have also shown that field emission characteristics are strongly dependent on the geometry of the CNT support structure due to electrostatic field screening [4] and on the cathode to anode gap separation [13][14][15]. Hence, the magnitude of R is also affected by the geometry of the devices as well as the structure of the CNT emitter itself.…”
Section: Carbon Nanotube Diode Modelmentioning
confidence: 66%
“…Finite element analysis reveals that varying the radius of a cylindrically shaped support structure from 0.5 to 30 lm results in an increase in the macroscopic turn-on field from 0.72 to 5.89 V lm À1 . Furthermore, the field enhancement factor decreases asymptotically for increasing support structure radius [4]. We have also demonstrated an improved fabrication technique for individual CNT emitters based on MEMS technology that enables a high degree of control over the cathode structure [5].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…PERFORMING ORGANIZATION REPORT NUMBER [2]. Also, our group presented an experimental and simulation investigation of the influence of cathode support structure geometry on the field emission properties of a single CNT emitter [3]. In this paper, we present an empirical study of dynamic behavior of an electron source system which incorporates an individual CNT.…”
Section: Performing Organization Name(s) and Address(es)mentioning
confidence: 99%